GROWTH OF ARCHAEAN CRUST IN THE KUHMO DISTRICT, EASTERN FINLAND: U-PB AND SM-ND ISOTOPE CONSTRAINTS ON PLUTONIC ROCKS - Käpyaho A.; Mänttäri I.; Huhma H. (My University, 2006)
Neoarchaean plutonism in the Kuhmo district in eastern Finland, Karelia, includes tonalites, sanukitoids, leucocratic granodiorites, and leucogranites. A U-Pb (SIMS and TIMS) study of zircons and titanites places age constraints on this plutonic activity, and whole-rock Sm-Nd isotopes are used to characterise source variation. U-Pb results indicate that the tonalites were emplaced during at least three separate periods; >2.81, ~2.78, and 2.76-2.74 Ga. The initial εNd values vary from +0.3 to +2.2, and suggest no major involvement of significantly older crust in the genesis of tonalites. The tonalites were followed by 2.74-2.70 Ga (possibly also 2.68 Ga) sanukitoids with initial εNd values of -0.7 to 1.2. Close temporal relations between the ~2.74 Ga tonalites and sanukitoids indicate that their genesis may be linked. Subsequent leucocratic granodiorites and leucogranites were emplaced at 2.70-2.68 Ga and commonly contain inherited zircons. The initial εNd values of these granodiorites and granites vary from +1.1 to -3.4, indicative of multiple magma sources. The general decrease in initial εNd values with decreasing age demonstrate progressive recycling of pre-existing crust, thus stressing the importance of crustal recycling as a process in forming the leucocratic granitoid rocks. Overall, the Archaean plutonic rocks of the Kuhmo district are temporally similar to those in the adjacent Russian Karelia, suggesting that 2.83-2.68 Ga was one of the most extensive periods of crustal growth throughout the Karelia craton. © 2006 Elsevier B.V. All rights reserved.
Keywords: ARCHAEAN; GRANITE; MAGMATISM; SANUKITOID; SM-ND; TTG; U-PB; Precambrian::Archean; Докембрий::Архей